PENGARUH FLEKSIBILITAS JAM KERJA, INTEGRITAS DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN BANK SYARIAH INDONESIA KANTOR CABANG MERDEKA KOTA LHOKSEUMAWE - Hamdani, Hamdani; Saleh, M. (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract: This paper provides a related study of employee performance. This study examines the impact of working hours flexibility, integrity, and job satisfaction on employee performance at Bank Syariah Indonesia Kantor Cabang Merdeka Kota Lhokseumawe. The population of this research is the employees of Bank Syariah Indonesia Kantor Cabang Merdeka Kota Lhokseumawe consisting of 100 employees of marketing positions. Data obtained directly by researchers during field observations, namely by directly entering the research area to be investigated, by distributing questionnaires to respondents, in this case employees of the marketing position of Bank Syariah Indonesia Kantor Cabang Merdeka Kota Lhokseumawe. Processing of the data obtained was done using SPSS Software (Statistics for Social Sciences) Version 20 for Windows. The results of this study indicate that working hours flexibility has a significant positive effect on employee performance while integrity and job satisfaction show insignificant results on employee performance. The implication for the company is that the better the application of working hours flexibility in the company, the higher the level of employee performance. However, if the implementation of integrity and employee satisfaction will make employee performance decline.Keywords: Work Hours Flexibility, Integrity, Job Satisfaction, Employee Performance